Music of Azerbaijan : From Mugham to Opera - Huseynova, Aida (Book collections on Project MUSE., 2016)
This book traces the development of Azerbaijani art music from its origins in the Eastern, modal, improvisational tradition known as mugham through its fusion with Western classical, jazz, and world art music. Aida Huseynova places the fascinating and little-known history of music in Azerbaijan against the vivid backdrop of cultural life under Soviet influence, which paradoxically both encouraged and repressed the evolution of national musics and post-Soviet independence. Inspired by their neighbors to the East and West, Azerbaijani musicians enjoyed a period of remarkable creativity, composing and performing the first opera and the first ballet in the Muslim East, establishing the region's first Opera and Ballet Theater and Conservatory of Music, and discovering ways to merge the modal lyricism of mugham with the rhythmic dynamics of jazz. Drawing on previously unstudied archives, letters, and documents as well as her experience as an Azerbaijani musician and educator, Huseynova shows how Azerbaijani musical development was not a product of Soviet cultural policies but rather grew from and reflected deep and complex cultural processes.